(3GdCMcGe aj GdMdGd hGdMQGes - (3jMji Hf GdMSjf Hf GdbGSe Hf EHQGgje GdMSfj GdYdhqj GdQSj, GdeYQha H GdgGOj pEdi GdnMqb, J (B298 (3g` s ((3Ydi Hf GdMSjf Hf YHO dGdg Hf CMeO Hf eMeO Hf jhSa GdHMjQi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi dGJQGg GdYjhf , hdGJMjW Hg GdXfhf , hdGjUag GdhGUahf s
(3BNQgG (B:s
(3hBNQg ef HGH (B( (3Gdbhd ai GdeSed jchf dg bQjH cGaQ abjQ (B) : (3bhdg (B: (3adjS ef GdeYQha Cf jTaY hjLhYG , hdG Cf jcJSi hjYQjG Je GdLRA GdChd ef LRFjf ef cJGH GdCMcGe hGdMeO ddg s
(3cJHJ GdYfGhjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B141s
(3JHUQGJ GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis